Multifaceted Studies of the DNA Interactions and In Vitro Cytotoxicity of Anticancer Polyaromatic Platinum(II) Complexes. Issue 26 (24th May 2016) - Pages, Benjamin J.; Sakoff, Jennette; Gilbert, Jayne; Rodger, Alison; Chmel, Nikola P.; Jones, Nykola C.; Kelly, Sharon M.; Ang, Dale L.; Aldrich‐Wright, Janice R.
Abstract: This study reports a detailed biophysical analysis of the DNA binding and cytotoxicity of six platinum complexes (PCs). They are of the type [Pt(PL )( SS ‐dach)]Cl2, where PL is a polyaromatic ligand and SS ‐dach is 1 S, 2 S ‐diaminocyclohexane. The DNA binding of these complexes was investigated using six techniques including ultraviolet and fluorescence spectroscopy, linear dichroism, synchrotron radiation circular dichroism, isothermal titration calorimetry and mass spectrometry. This portfolio of techniques has not been extensively used to study the interactions of such complexes previously; each assay provided unique insight. The in vitro cytotoxicity of these compounds was studied in ten cell lines and compared to the effects of their R, R enantiomers; activity was very high in Du145 and SJ‐G2 cells, with some submicromolar IC50 values. In terms of both DNA affinity and cytotoxicity, complexes of 5, 6‐dimethyl‐1, 10‐phenanthroline and 2, 2′‐bipyridine exhibited the greatest and least activity, respectively, suggesting that there is some correlation between DNA binding and cytotoxicity. Abstract : A frame of bind : DNA binding behaviour of six polyaromatic platinum anticancer complexes has been studied using six biophysical methods (linear dichroism pictured), resulting in a comparison of the merits of each technique and the establishment of trends in DNA affinity in relation to complex structure. In vitro cytotoxicity in a panel of human cells was determined, revealing submicromolar activity in Du145 and SJ‐G2 cells. Correlations between activity and DNA affinity were determined.